(untitled) (International Journal of Engineering and Computer Science, 2015)
This paper outlines an interactive-object recognition system for the blind students using the Radio-frequency identification (RFID). RFID appears as an effective solution for object identification. This paper also gives a overview of the Radio-frequency identification technology and identification. Using a low frequency Radio-frequency identification integrated indoor environment, a framework was created to assist the blind to interact and identify with their surroundings with audio messages. The framework created uses an Arduino- Atmega328 micro-controller interfaced with a Low Frequency Reader Module. The RFID reader recognizes objects carrying passive small tags through unique, distinct codes. The object code, name and other details are logged into a Processing Script integrated with Redis DB and audio librariesthrough Serial Communication. This system successfully identifies various objects irrespective of their shape, size and physical attributes.